PROBLEMS OF PRESERVATION AND FORMATION OF KHANAKA OF UZBEKISTAN - Kamilova M.E.; Mukhamadieva N.U.; Adilova. D.S. (Academia Science Repository, 2023)
This article examines the role and place of the Sufi khanaka in the architecture of Uzbekistan and the effective preservation of these architectural monuments.